Evaluasi Program Pelayanan Kesehatan Peduli Remaja di Puskesmas Sukapakir Kota Bandung Menggunakan Perspektif Model CIPP - Paundria S W, Raissa Kusuma; Prasetyo, Pius Sugeng (Department of Public Administration, Parahyangan Catholic University, 2024)
This study aims to evaluate the Adolescent Care Health Service Program at Puskesmas Sukapakir Bandung City through the perspective of the CIPP model by analyzing the context, input, process, and output of the Adolescent Care Health Service Program at Puskesmas Sukapakir Bandung City. This research was conducted using qualitative research methods with descriptive research type. This research was conducted with primary data sources obtained by interviewing the person in charge of the Youth Care Health Service Program at the Sukapakir Health Center in Bandung City and secondary data obtained from journals and previous research on the evaluation of the Youth Care Health Service Program at the Sukapakir Health Center in Bandung City. Data collection techniques used by observation, interviews, and documentation. In analyzing the data, it was analyzed using content analysis. Based on the results of the discussion, it was found that in the context evaluation which discussed whether the program was held following the needs, the author found the suitability between the needs of adolescents and the objectives of the Adolescent Care Health Service Program at the Sukapakir Health Center in Bandung City, then the input evaluation analyzed the parties who played a role, the source of funds and infrastructure. The results showed that there were adequate human resources according to their fields, as well as the provision of financial resources and the availability of facilities and infrastructure. In the process evaluation, it was found that in its implementation there was a clear time every quarter and it was held effectively by combining the Adolescent Care Health Service Program at Puskesmas Sukapakir with other programs. In the product evaluation, the Adolescent Care Health Service Program at Puskesmas Sukapakir Bandung City is said to be quite successful even though there are sectors that have not significantly developed.